Fixed-wing vertical-takeoff-and-landing UAV with additive manufacturing : a dual-rotor version - Gokhale, Ruddhi (2018)
Amongst the two main types of fixed-wing vertical-takeoff-and-landing (FWVTOL) unmanned aerial vehicles (UAVs) namely, hybrid fixed-wing multicopter UAVs and tiltrotor FW-VTOL UAVs, the latter is usually preferred due to its efficient propulsion system that is utilized for all flight phases. Howbeit, in the currently available tilt-rotor FW-VTOL UAVs, one or more rotors are turned off during the FW mode, which eventually acts as a dead weight for the UAV. Therefore, in this paper, we design a tilt-rotor FW-VTOL UAV which encompasses a dual-rotor configuration. The enticing features of this UAV includes its weight optimized design along with the inclusion of flaperons that serve three purposes: provide roll control during FW mode, generates additional lift during transition, and reduces blockage to the airflow of the main rotors during VTOL mode. In addition, we prototype it utilizing additive manufacturing (AM) as the primary manufacturing method. The high strength and rapid prototyping features of AM are utilized in our design to achieve adequate structural strength without inducing weight penalties. What is more, experimental tests in the VTOL mode are conducted to verify the design feasibility. The results exhibit that AM is a promising manufacturing method for complex FW-VTOL UAVs, wherein its on-demand printing ability significantly lowers the overall development cost.